The truth about background and reference checks when hiring - Fyock, Catherine D. (FTPress Delivers elements., 2011)
This Element is an excerpt from The Truth About Hiring the Best (9780132381864) by Cathy Fyock. Available in print and digital formats. How to ferret out and avoid "scam-didates": job candidates who flat-out lie about their credentials and experience. The candidate you're interviewing appears to have everything--the right background, perfect experience, and all the credentials you're looking for. But it's too good to be true. And this is about more than just spin: It's outright lying. Statistics reveal that nearly 36% of applications are falsified!